PERBEDAAN KEPATUHAN TIM BEDAH DALAM PELAKSANAAN SURGICAL SAFETY ANTARA PASIEN OPERASI ELEKTIF DAN EMERGENCY DI RSU KARSA HUSADA KOTA BATU - Nanda Priatna; rudi hamarno; rony yuliwar (Jurnal Keperawatan Terapan, 2019)
Patient safety with surgery becomes the main focus in medical action, as it involves invasive procedure. The obidience of surgical team is very important to reduce the risk at the surgery procedure. At 2007, WHO has released a method for keep the patient safety in Surgical Safety Checklist (SSC) form, to reduce the mortality of patient. The purpose of this research is to know the difference of obidience of surgical team in implementation of surgical safety between elective and emergency surgical patient at operating room of Karsa Husada Hospital. The research design that used is comparative design with cross-sectional approach, with the amount of sample is 22 person and used the purposive sampling according to the both inclusion and exclusion criteria. The method of collecting data implemented by non-participative observation to the surgical team that conducting the operation each 15 times to both the elective dan emergency surgery patient. The research instrument that used was SSC observation form. The tabulating data that used was analytic comparative technic with Chi Square test. The results show the obidience of surgical team in surgical safety checklist implementation at elective surgical patient is 80% was scored obey, meanwhile at emergency surgical patient is only 7% was scored obey, and the significance score is 0,000, that means there is a difference of obidence of surgical team in the implementation of surgical safety between elective and emergency surgery patient. Keywords: Obedience, surgical team, surgical safety, elective, emergency